Identification of a virulence-associated antigen of Toxoplasma gondii by use of a mouse monoclonal antibody. - Gross, U (1991)
A monoclonal antibody generated against the mouse-lethal RH strain of Toxoplasma gondii was developed. Tachyzoites of virulent and avirulent T. gondii isolates grown in permanent macrophage cell cultures were examined for differences in reactivity with this antibody. Virulence of these Toxoplasma isolates was quantified by injecting different numbers of tachyzoites into NMRI mice and observing the animals for signs of infection or death. The monoclonal antibody identified a 23-kDa antigen expressed by the mouse-lethal strains BK and RH, whereas this antigen was not detected in low-mouse-virulent strains, which were all clinical isolates from Europe. Using Western blot (immunoblot), immunofluorescence, and immunoelectron microscopy, we localized the 23-kDa antigen to the membrane compartment. From these results, we suggest that this 23-kDa antigen is a marker of strain virulence upon which a virulence classification of T. gondii may be based.